Nine historical views of the Phillips curve: eight authentic and one inauthentic - Forder, J (World Scientific Publishing, 2021)
There is a widely believed but entirely mythical story to the effect that the discovery of ‘the Phillips curve’ was, in the 1960s and 1970s, an inspiration of inflationist policy. One aspect of the explanation of how that myth came to be widely believed is considered in this paper. It is noted that the expression ‘Phillips curve’ was applied in a number of quite distinct and inconsistent ways, and as a result there was, by about 1980, an enormous confusion as to what that label meant. This confusion, as well as the multiplicity of possible meanings, it is suggested, provides part, although only part, of the explanation of the myth’s acceptance.